In vivo NMR spectroscopy : principles and techniques - De Graaf, Robin A (John Wiley, 1998)
In Vivo NMR Spectroscopy Robin A. de Graaf Department of in vivo NMR, Utrecht University, The Netherlands This is the first book in the field of in vivo NMR to cover in depth the technical and basic biophysical aspects of the technique. The contents of the book are appropriate to both beginners and experienced users of in vivo NMR spectroscopy. The book has also a practical setup, allowing readers to incorporate the presented concepts into their own MR research. An extensive treatment of radiofrequency pulses is given, together with several tables and recipes for their generation. A practical approach is followed in describing spatial localization and the pros and cons of all known water-suppression techniques. In addition, 2-D NMR, magnetic resonance imaging, spectroscopic imaging, spectral editing and many basic principles are explained and illustrated using practical examples. Several tables containing basic biophysical information, such as resonance frequencies, diffusion coefficients, relaxation constants, and absolute concentrations are also presented. The educational and practical character of this book makes it ideal for use in training courses at large research institutes and academic hospitals. In general, all those involved in fundamental and/or diagnostic in vivo NMR will find this book useful. This can range from people working in dedicated in vivo NMR institutes to radiologists working in hospitals. Also, those who want to broaden their knowledge on the concepts of NMR, such as researchers in high-resolution NMR, neurology, physiology, chemistry, and medical biology will benefit greatly from this book.
Keywords: nukleární magnetická rezonance biomolekulární; Nuclear Magnetic Resonance, Biomolecular; radiologie, nukleární medicína a zobrazovací metody